Tandem Solar Cells: Spatially and Spectrally Resolved Absorptivity: New Approach for Degradation Studies in Perovskite and Perovskite/Silicon Tandem Solar Cells (Adv. Energy Mater. 4/2020). Issue 4 (28th January 2020) - Nguyen, Hieu T.; Gerritsen, Sven; Mahmud, Md Arafat; Wu, Yiliang; Cai, Ziyuan; Truong, Thien; Tebyetekerwa, Mike; Duong, The; Peng, Jun; Weber, Klaus; White, Thomas P.; Catchpole, Kylie; et al.
Abstract : In article number 1902901, Hieu T. Nguyen and co‐workers employ spectrally and spatially resolved absorptivity at sub‐bandgap wavelengths of perovskite materials, extracted from their luminescence spectra, to study degradation across perovskite and perovskite/silicon tandem solar cells. The absorptivity is demonstrated to reflect real degradation in the perovskite film and is much more robust and sensitive than its luminescence spectral peak position, representing its optical bandgap and intensity.